The Dignity of Democracy in the Appointment of Acting Regional Heads by the President: Legal Construction After the Constitutional Court Decision Number 15/PUU-XX/2022 - M Riadhussyah; Farhan Farhan; Fathul Hamdani; Lalu Aria Nata Kusuma (Universitas Muhammadiyah Surakarta, 2022)
Purpose of the study: The purpose of this study is to examine the legality of the position and authority of the acting regional head, as well as to examine the dignity of democracy in the appointment of acting regional heads by the president and its construction after the Constitutional Court Decision Number 15/PUU-XX/2022. Methodology: This study applies normative legal research methods using a statutory, conceptual, and case approach. Results: The results of the study show that the appointment of acting regional heads is the operationalization of the concept of politically appointed presidential power and not the concept of election (political elected) as regional heads. The consequence is a lack of regional legitimacy and a lack of relations with the people because it is not the people's choice. This condition shows a portrait of the decline of democracy in the regions. In this case, the government should prepare by making implementing regulations related to the mechanism for selecting regional heads by not degrading the democratic values as mandated by the Constitutional Court in its decision Number 15/PUU-XX/2022. Applications of this study: This article provides an analysis of how democratic principles should still be applied in the process of appointing acting regional heads. This research is expected to be useful and can be a reference material for those who conduct research, especially with regard to the appointment of the acting regional head. Thus, this research is expected to enrich the scientific treasures and studies related to the mechanism for appointing acting regional heads. Novelty/ Originally of this study: The research related to the appointment of acting regional heads is still very minimal. So with the research that examines the dignity or portrait of democracy in the mechanism for appointing the acting regional head, it is considered very important as reference material in the process of implementing democracy in Indonesia.